2015
DOI: 10.1177/1545968314568726
|View full text |Cite
|
Sign up to set email alerts
|

Corticopontocerebellar Connectivity Disruption in Congenital Hemiplegia

Abstract: Disruption of structural cerebrocerebellar connectivity is present in patients with congenital unilateral brain injury and might be related to impaired hand function in bimanual skills, with potential implication in tailoring early intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Powell et al () reported leftward cerebellar asymmetry in both right‐ and left‐handed healthy individuals, and Takao et al () reported leftward cerebellar asymmetry in a healthy right‐handed population; this is similar to the findings of the present study. Fiori et al () found asymmetry of the CPCT in a healthy control group consisting of young children, but no laterality, nor the degree of the asymmetry, were described. In a DTI‐based clinical trial investigating chronic stroke, the healthy control group showed no significant difference in FA between the right and left MCP (Schulz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Powell et al () reported leftward cerebellar asymmetry in both right‐ and left‐handed healthy individuals, and Takao et al () reported leftward cerebellar asymmetry in a healthy right‐handed population; this is similar to the findings of the present study. Fiori et al () found asymmetry of the CPCT in a healthy control group consisting of young children, but no laterality, nor the degree of the asymmetry, were described. In a DTI‐based clinical trial investigating chronic stroke, the healthy control group showed no significant difference in FA between the right and left MCP (Schulz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This organization poses a key problem for diffusion-tensor-based tractography, that of following crossing fibers. Thus, in this work a non-tensor model combining CSD algorithm with probabilistic tractography 13 , 14 , 37 was adopted, as already successfully done for the CTC pathway reconstruction 9 . Some fidelity to the known anatomical characteristics of the CPC pathway was imposed by using a relatively unconstrained approach (ROIs were placed in the MCP and in the CP, allowing streamlines to freely reach any cortical areas), and the resulting cerebral and cerebellar areas involved in the reconstructed pathway were in agreement with the anatomical findings of ex vivo experiments 4 , 17 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the fact that MRI tractography cannot distinguish between efferent and afferent tracts implies that the direction of axon potential propagation has to be inferred using a priori knowledge. Indeed, we placed seed/target ROIs on the basis of findings from anatomical studies 17 , 18 and on the basis of previous tractography studies 7 , 13 demonstrating that the streamlines passing through the CP and the MCP can be identified as part of the major bundle unidirectionally connecting the cerebral cortex to the cerebellum. Despite of, the reconstructed streamlines, “upstream” of CP and “downstream” of MCP, were allowed to run unconstrained towards the cerebral and cerebellar cortices, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that systematic classification of lesions on T1 weighted MRI images as unilateral or bilateral is reliable; in unilateral lesions white matter differences are restricted to the lesioned hemisphere, despite the corpus callosum being affected across the midline in the right hemiparesis group. These differences between right and left hemiparesis could be the result of differences in brain lesions (see sqMRI scores in 113 . Further study on each of these regions is warranted, in particular a structure function relationship should be established where possible.…”
Section: Discussionmentioning
confidence: 99%
“…The corticopontocerebellar tracts were shown to have an increased asymmetry (based on streamline count) in children with unilateral spastic CP, and this was shown to correlate with Assisting Hand Assessment scores 113 . The medial lemniscus was also studied, and shown to have reduced FA in children with unilateral CP who had normal structural MRI; this cohort was also not found to have any significant FA or MD changes in either the corticospinal tract or the posterior thalamic radiations 185 .…”
Section: Extrapyramidal Motor Pathwaysmentioning
confidence: 95%